Urgent Chemotherapy for Life-Threatening Complications Related to Solid Neoplasms. Issue 7 (July 2017) - Zerbib, Yoann; Rabbat, Antoine; Fartoukh, Muriel; Bigé, Naïke; Andréjak, Claire; Mayaux, Julien; De Prost, Nicolas; Misset, Benoît; Lemiale, Virginie; Bruneel, Fabrice; Maizel, Julien; Ricome, Sylvie; et al.
Abstract : Objectives: Solid neoplasms can be directly responsible for organ failures at the time of diagnosis or relapse. The management of such specific complications relies on urgent chemotherapy and eventual instrumental or surgical procedures, combined with advanced life support. We conducted a multicenter study to address the prognosis of this condition. Design: A multicenter retrospective (2001–2015) chart review. Setting: Medical and respiratory ICUs. Patients: Adult patients who received urgent chemotherapy in the ICU for organ failure related to solid neoplasms were included. The modalities of chemotherapy, requirements of adjuvant instrumental or surgical procedures, and organ supports were collected. Endpoints were short- and long-term survival rates. Interventions: None. Measurements and Main Results: One hundred thirty-six patients were included. Lung cancer was the most common malignancy distributed into small cell lung cancer ( n = 57) and non-small cell lung cancer ( n = 33). The main reason for ICU admission was acute respiratory failure in 111 patients (81.6%), of whom 89 required invasive mechanical ventilation. Compression and tissue infiltration by tumor cells were the leading mechanisms resulting in organ involvement in 78 (57.4%) and 47 (34.6%) patients. The overall in-ICU, in-hospital, 6-month, and 1-year mortality rates were 37%, 58%, 74%, and 88%, respectively. Small cell lung cancer was identified as an independent predictor of hospital survival. However, this gain in survival was not sustained since the 1-year survival rates of small cell lung cancer, non-small cell lung cancer, and non-lung cancer patients all dropped below 20%. Conclusions: Urgent chemotherapy along with aggressive management of organ failures in the ICU can be lifesaving in very selected cancer patients, most especially with small cell lung cancer, although the long-term survival is hardly sustainable. Abstract : Supplemental Digital Content is available in the text.